Comparison of Agathis philippinensis resin tapping and collection practices in three selected sites in the Philippines (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Daracan VC, Mendoza RC, Torres AM, Jara AA, Manalo RD, Batallones CHR, Razal RA. 2020. Comparison of Agathis philippinensis resin tapping and collection practices in three selected sites in the Philippines. Biodiversitas 21: 5595-5604. This study documented and compared almaciga (Agathis philippinensis Warb.) resin tapping and collection practices in three sites namely Mt. Hamiguitan, Governor Generoso, Davao Oriental; Mt. Mantalingahan, Brooke’s Point, southern Palawan; and Puerto Princesa Subterranean River National Park, Marufinas, central Palawan. Resin tappers, mostly male belonging to a local organization, were interviewed, and tapping sites were visited. Tapping and collecting A. philippinensis resin is one of the supplemental income sources of the respondents from the three sites. Market influences, and how tappers learned the trade could partly explain the similarities and differences in tapping practices. Discrepancies in selecting trees to be tapped, tools used, type of incisions made on the bark, and how resin was harvested were noted. Differences in resin appearance across sites were observed, and the existence of uncollected and wasted resins clinging to trees or sprawling at its base was found in all sites. Removing dirt from the portion of the stem to be tapped, covering the bark incision with plastic for protection, and contriving handmade resin baskets from plant parts available in the site were some practices found to be worth replicating. On the other hand, there were damaged or dying trees due to the intensity of tapping, the lack of tapping skills, and limited attention given to the health of trees. There is a need for strengthening tappers’ organizations for increased bargaining power to secure better resin price and policy support to prioritize indigenous peoples in tapping into their ancestral domain. Tappers can benefit from cross-visits and other learning opportunities for sharing lessons and experiences to improve tapping practices for better resin quality and higher prices.
Keywords: Agathis philippinensis, almaciga, indigenous knowledge, local tappers, resin yield, supply chain